Research on Elementary Reading Critical and Interpretive Reading. ERIC/CRIER Reading Review Series, Volume 2, Bibliography 19 - Smith, Carl B., Comp.; Roser, Nancy, Comp.; Indiana Univ., Bloomington ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1969)
This bibliography of research studies on critical and interpretive elementary reading is divided into two major parts. In Part I, which includes reports published since 1950, subsection A contains citations and abstracts for highly relevant reports focusing specifically on critical and interpretive reading. Subsection B contains a citation and short annotation for those reports which make a relevant statement about critical and interpretive reading but whose main focus lies outside these areas. Subsection C reports studies related in a peripheral manner to these two subject areas. In Part II, reports published between 1900 and 1949 are listed alphabetically according to the author's last name without being classified in terms of relevancy. A citation and annotation are included for each item. This publication is one of a series of bibliographies related to reading in the elementary school, and the seven basic references of the ERIC/CRIER document collection were used as the source of the citations. Information for ordering the cited documents in hard copy or microfiche form from ERIC Document Reproduction Service is included. (CM)
Educational level discussed: Elementary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Context Clues; Creative Reading; Elementary Education; Reading Comprehension; Annotated Bibliographies; Critical Reading; Interpretive Reading; Reading Research